(untitled) (SCHOOLAR: Social and Literature Study in Education, 2023)
The implementation of Islamic Religious Education learning in schools is a teaching and learning process which is an aspect of an organized school environment. This environment is regulated and monitored so that the implementation of the teaching and learning process is in accordance with educational goals. it can be concluded that the implementation of PAI learning in Hasbullah Tambakberas Jombang Creative Vocational School is the initial plan for the formation of an effective and easily accepted teaching process by students. This learning strategy is used as the main reference in order to achieve the goal of implementing PAI learning in Hasbullah Creative Vocational School Tambakberas Jombang. In this study, the research approach used is a qualitative approach. It is said to be a qualitative approach because this study seeks to reveal the symptoms as a whole in accordance with the context through the collection of data in a natural setting with the researcher as the main instrument and to emphasize process and meaning from the point of view of the researched subject. In the implementation of PAI learning at Hasbullah Tambakberas Jombang Creative Vocational School, teachers have used the media to help clarify learning understanding to their students. Teachers have also taken advantage of the use of the internet because the use of the internet is seen as not only capable of being a source of learning other than teachers, or printed books, but the internet can also be an effective learning medium. The application of the Power Of Two method is based on the view that students already have knowledge or understanding of topics or problems related to the learning topics to be studied.